DEMOCRACY AND IMPROVEMENT OF ECONOMIC LEGISLATION - Юлдашев, Сергій Олексійович; Юлдашев, Олексій Хашимович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to study the problems of democracy as a tool to achieve political and economic goals, justify the possibility and feasibility of using the institute of democracy as a means of improving the quality of economic governance, improving economic legislation. Methods of research: general scientific which gave an opportunity to analyze the essence of democracy, to investigate the issues of improvement of law-making activity, normative-legal acts; the method of analysis and synthesis allowed us to formulate proposals for using the institute of democracy as a tool for improving economic legislation. Results: the essence of democracy was analyzed, the issues of improvement of law-making activity were investigated; the method of analysis and synthesis allowed us to formulate proposals for using the institute of democracy as a tool for improving economic legislation. Discussion: problems of forms of exercising democracy, their positives and risks, drafts of relevant legislative acts, proposals for their improvement. The problems related to the exercise of democracy, the risks of holding referendums and the improvement of lawmaking have been investigated - remain unresolved and, on the basis of their relevance, in need of immediate resolution. There are two types of referendums. The first are those that have legally significant results, are binding decisions (such referenda are considered political), and the second are those that are not, do not have the status of legally significant. Forms of second-party national wills that do not have legally significant results are not binding solutions. Such forms should include not only all kinds of meetings, rallies, appeals, discussions of bills, but also various sociological polls, social networks, meetings, speeches at rallies, in the media (except for official speeches), electronic petitions, etc. Such forms of exercising democracy could be a powerful factor in improving economic legislation. We have developed a project, built a model of redistribution of central power (one that came from the USSR) between the central apparatus of economic management, local authorities and the non-state sector in accordance with the relevant European models. On the use of democracy as a means of improving the quality of economic governance, improving economic legislation. It is proposed not to change people (old faces to new and vice versa), but to change the organizational conditions in which the power holders work. It is about designing a qualitatively different organization, a system of management without «investment nannies», which is «sharpened» under effective management, development of Ukraine as an information society, an innovation hub, a knowledge society. The transition to a new system of public administration is a prerequisite for a powerful budget filling precisely at the expense of internal organizational reserves, ensuring the independence of the state, withdrawing it from foreign influence. In the proposed system, it will not be possible to steal budget funds first and secondly to make inefficient management decisions. The implementation of such a model will be accompanied by the restructuring of education and science, the implementation of appropriate judicial reform and the reform of the law enforcement system. At the heart of the reform is a moratorium on the «updating» of law enforcement personnel, the judiciary, and other components of the judiciary. All the attention is paid to the organizational conditions of decision-making (including judicial), ensuring their legality, validity and fairness. All this will significantly increase the main economic indicators by an order of magnitude. There is no need to sell the latter - strategic businesses, land, legalize gambling, drugs, prostitution. We will not shudder (at least for any investment), but will choose the best deals. The country from the poorest in Europe in two or three years will turn into the most successful with all social consequences - instead of centrifugal tendencies, opposite will appear - the center of aspiration - to us will run from abroad, and not only Ukrainians. The same will be true of investments. The introduction, in order to increase the efficiency of legislative activity, the problem-oriented approach, would help to systematize the problems of the country’s life, as well as ideas for solving them. And such problems and ideas are contained in analytical materials, relevant proposals for improvement of the situation, which are contained in speeches of citizens, various experts at meetings, rallies, in appeals of citizens, in materials on discussing bills, analyzes of various sociological polls, social networks, speeches in the media, on television shows, in electronic petitions. Appropriate registers need to be created - a registry of problems and a register of ideas. The latter should include proposals provided in scientific papers - scientific reports, dissertations. Population of registration and reference character (such as E-child), but how much automation of state administration, the process of lawmaking by conducting in computerized mode (systematization, analysis, search) of computer databases - banks with registers of problems and ideas, preparation and evaluation of alternative solutions, draft laws.